ZOOPERYFITON RIVER WET MOSKOVKA WITHIN THE CITY OF ZAPORIZHIA AND SELF-PURIFICATION PROCESSES LOTYCHNYH AQUATIC ECOSYSTEMS - , К. О., А. О., О. І. (Municipal economy of cities (Technical science), 2013)
The problems associated with the study communities zooperyfitona on various solid substrates small rivers and their role in the self-cleaning of the watercourse